Carbonate complexes underlying Flysch belt and subsurface Neogene volcanic in the NE part of Slovakia – a potential for geothermal energy and raw materials - KUCHARIČ, Ľudovít; BEZÁK, Vladimír; MAJCIN, Dušan; VOZÁR, Ján (Contributions to Geophysics and Geodesy, 2012)
A positive gravity anomaly was observed in the Flysch belt realm. Based on this fact and available geological knowledge we suppose that the source of gravity anomaly might be carbonate rocks lying perhaps in the footwall of Flysch sediments. The carbonates belong perhaps to the Penninic crust cover (a part of Klippen belt), or to lower structural stage of the Flysch belt. Besides this it is interpreted more volume of Neogene subvolcanic bodies in the frame of the Flysch belt based on the results of the newest magnetic measurements in the NE part of Slovakia (Kucharič et al., in press). These are accompanied by increasing heat flow and hydrothermal alteration within neighbouring rocks what may eventuate into creation of raw materials. These two factors – carbonates and subvolcanic bodies – are important items for appraisal of new perspective in this area not only from hydrocarbon occurrences point of view (a primary intend within this area) but also for enhancement of geothermal potential of Slovak Republic and opening possibilities for prognosis of raw material occurrences as well.